Foundations of Trusted Autonomy - Abbass, Hussein A.; Scholz, Jason; Reid, Darryn J. (Studies in Systems, Decision and Control, 2018)
Trusted Autonomy; Automation Technology; Autonomous Systems; Self-Governance; Trusted Autonomous Systems; Design of Algorithms and Methodologies